O contexto da Educação Infantil: implicações da gestão escolar na prática pedagógica - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
This study has as object of research the school management in the pedagogical practice of the kindergarten. The research is characterized as qualitative (GHEDIN; FRANCO, 2008) and has the following problematic question: How is school management effective in the pedagogical practice of early childhood education? The research has the following objectives: To analyze the performance of school management in pedagogical practice in early childhood education; Unveil the organization of school management in relation to pedagogical practice in early childhood education; To investigate the implications of school management in the organization of pedagogical practice in early childhood education. This thesis considers the assumption that in various aspects of the organization of pedagogical work in early childhood education, school management resembles that of elementary school, so the thesis we defend is that for the concreteness of school management in early childhood education there is a need to planning, intentionality, reflexivity, collective work, and assessment that meet the specificities of childhood and the characteristics of children. We used as theoretical support for the development of this study in relation to the pedagogical practice the studies of Vazquez (1977), Franco (2008, 2014) and Gimeno Sacristán (1999, 2007); To discuss school management we use the studies by Bosco de Lima (2011), Domingues (2014), Franco (2008, 2014); Hypólito (2008), Libâneo (2004) and for the discussion of the Pedagogical Political Project are used the studies of Caria (2011), Bondioli (2009), Pinto (2011), Veiga (2003). Regarding the discussions of kindergarten we will discuss with the authors Rocha (1997), Carvalho (2005, 2015, 2016) Carvalho and Fochi (2016, 2017), Carvalho and Guizzo (2018); Formosinho, Kishimoto and Pinazza (2007). The research was carried out in three Municipal Centers of Early Childhood Education (CMEI) in the city of Ponta Grossa/PR. The participants of the research were three (3) pedagogical coordinators, three (3) principals and thirty-one (31) teachers of the CMEIS participants. As instruments for data collection we used the document analysis, the questionnaire and the semi-structured interview. The organization, analysis and discussion of the research data was based on the theoretical methodological assumptions of Content Analysis (BARDIN, 2011) and Data Triangulation (TRIVIÑOS, 2008). The main conclusions of this research are as follows: the discourse of neoliberal quality, directed to schooling is also part of early childhood education; there is persistence of a pedagogical way of ignoring the rights of children, due to the bureaucracy present in the preschool; the child still does not occupy centrality in the pedagogical actions of the Early Education. In this study, we point out the relevance of school management in early childhood education, we also highlight that at this stage of Basic Education, the organization of pedagogical work and pedagogical actions need to be rethought. Thus, through this research, we seek to contribute to studies on school management in early childhood education, as well as to propose considerations that allow reflections and discussions about the implications of school management in the pedagogical practice of early childhood education, considering the specificities of childhood. and the characteristics of children.
Keywords: Gestão escolar; Prática pedagógica; Educação Infantil; School management; Pedagogical practice; Children's Education; CNPQ::CIENCIAS HUMANAS::EDUCACAO